Impact of Oil Price, Exchange Rate and Capital Structure on Firm Performance: Evidence from Nairobi Securities Exchange - David Onguka (European Scientific Journal, ESJ, 2019)
This study aimed at determining the impact of oil prices, exchange rate and capital structure on the Performance of NSE listed firms. Annual data include oil prices, exchange rates, debt-equity ratio and firm performance are modeled into a linear regression model. The annual average international prices of the three oil products prices of Diesel oil, Premium and Kerosene were used as these are the major consumed products in Kenya. Hypothesis were formulated and tested on a population of sixty four listed firms at the NSE. The study used petroleum prices obtained from Energy Regulatory commission website, global prices obtained from plats, exchange rates from CBK, leverage and return on Assets (ROA) from audited financials obtained from NSE year books. The study applied census survey due to the small size of the population of firms listed at the NSE. The findings show there is significant relationship between oil price changes, exchange rate, capital structure and company performance.